Kinerja Struktur Rumah Joglo terhadap Beban Gempa dan Implikasi bagi Desain Hunian Modern - Totok Harmoyo; Kahar Sunoko; Avi Marlina (Universitas Sebelas Maret Surakarta, 2026)
Structural Performance of a Joglo House under Seismic Loads and Implications for Modern Residential DesignQuantitative studies on the structural resilience of joglo houses in earthquake-prone areas are limited, necessitating scientific analysis to ensure safety. This study analyzes the structural behavior of a joglo house in Dusun Jendi, Selogiri District, Wonogiri Regency, using the finite element method (FEM) through three-dimensional structural modeling in SAP2000. Data were obtained from field surveys, including element dimensions, timber material properties, and traditional joint systems. The analysis incorporated combined gravity and seismic loading in accordance with Indonesian National Standards (SNI). The results indicate that the joglo structure exhibits a hierarchical load distribution mechanism, transferring loads from the roof to horizontal elements (blandar), the main vertical elements (soko guru), and the foundation. Modal analysis identified three dominant vibration modes, namely lateral displacements and torsional rotation. The blandar resists the largest bending forces, while the soko guru carries the highest axial loads, indicating stable and earthquake-adaptive structural performance.